PENGARUH TRANSAKSI HUBUNGAN ISTIMEWA TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR NON KEUANGAN YANG TERDAFTAR DI BEI TAHUN 2012-2015 - ZUBAIDAH, LILIK; DUDY SETYAWAN, MADE (Jurnal Akuntansi AKUNESA, 2017)
Tax is the largest source of state revenue. The difference of importance between taxpayer and government cause occurrence tax avoidance, one of them through a related party transactions. This research aims to examine the effect of related party transactions (sale, purchase, and loan transactions) toward tax avoidance as measured by effective tax rate. This research uses quantitative research type. The population in this research includes non-financial sector companies listed on Indonesia Stock Exchange from 2012 until 2015 with purposive sampling as sampling method. The result of multiple linear regression analysis shows that related party transaction-sales and related party transaction-loan haven?t effect on tax avoidance. While related part transaction-purchase have effect on tax avoidance.